The Influence of pH, Acidity, and Sugar Content on the Taste and Quality of Tomato Paste - Najat M. Aburas; Maryam M. Alajami; Zuhra A. Aissa (African Journal of Advanced Pure and Applied Sciences, 2025)
This study reviewed some of the chemical and physical properties of twenty tomato paste samples, measuring pH, total titratable acidity, and sugar content as quality and safety criteria. Twenty commercial samples were analyzed using standard methods, including titration, a pH meter, and high-performance liquid chromatography (HPLC). Most samples yielded results within the permissible limits of pH ≤ 4.6, with the exception of three samples that exceeded this limit, increasing the potential for the growth of some microbes, such as Clostridium botulinum. The total acidity resulting from titration ranged between 32,698 and 44,810 mg/kg, which remains below the maximum permissible limit of 7% (70,000 mg/kg). The sugar content showed significant variation, with 15 samples exceeding the permissible limit of 12 mg/kg, indicating the potential for sugar addition during manufacturing and processing. The study emphasizes the need for strict regulation and monitoring of pH, sugar content, and the use of advanced analytical methods, such as Fourier transform infrared spectroscopy (FT-IR), to enhance quality control and consumer protection.